Some Extensions and Generalizations of Kümmer's Third Summation Theorem - Qureshi, Mohammad. I.; Khammash, Ghazi; Bhat, Aarif. H.; Majid, Javid (Al-Mukhtar Journal of Sciences, 2022)
The motive of this research paper is to obtain explicit forms of certain extensions and generalizations of Kümmer's third summation theorem, which have not previously appeared in the literature, by using the summation theorem given by Rakha and Rathie (2011). The results derived in this paper are interesting and may be beneficial.